A pilot study of low-cost, high-resolution microendoscopy as a tool for identifying women with cervical precancer - Pierce, Mark C (2012)
Cervical cancer remains one of the leading causes of death among women in developing countries. Without resources to support Pap smear cytology and colposcopy, cost-effective approaches which enable single-visit “see-and-treat” protocols offer the potential to reduce morbidity and mortality due to this preventable disease. We carried out a pilot clinical study in Shanxi province, China, to evaluate a low-cost, high-resolution microendoscope (HRME) imaging system which enables evaluation of epithelial cell morphology in vivo. HRME images were obtained at discrete sites on the cervix in 174 women, in addition to visual inspection with acetic acid (VIA), and colposcopic examination. Out of 69 sites appearing abnormal on colposcopy, only 12 showed high-grade disease (CIN2+) on pathology. Quantification of the nuclear-to-cytoplasm ratio by HRME enabled an ad hoc threshold to be defined, which correctly classified all 12 sites as abnormal, whilst classifying 38 of the remaining 57 pathology normal sites as normal. All patients with biopsy confirmed high-grade disease also tested positive for high-risk HPV DNA, and were classified as abnormal by HRME. Among the remaining patients who tested positive for HPV but were either normal by colposcopy or showed < CIN2 on pathology, only 6/32 (18.8%) were classified as abnormal by HRME. Visual examination techniques for cervical cancer screening may overestimate the prevalence of precancerous lesions, leading to unnecessary treatment, expense, and patient stress. The results of this study suggest that evaluation of suspicious lesions by HRME may assist in ruling out immediate cryotherapy, thus increasing the efficiency of current see-and-treat programs.